Financial Ratios and These Effects Toward Sukuk Yield with Sukuk Risk as a Mediator Variable - Muhamad Abduh; Fitri Sri Handayani (Review of Islamic Economics and Finance, 2022)
AbstractPurpose - This study aims to demonstrate the impact of financial ratios on sukuk yield using sukuk risk as a mediator variable.Methodology - This study focused on corporations in general and employed path analysis and the Sobel test. The secondary data used for this study spans the years 2017 through 2019, with a total of 33 sukuks still outstanding for each year. Findings-According to the study's findings, corporate liquidity has little bearing on sukuk yield or risk. Corporate leverage, meanwhile, has a positive impact on sukuk yield and a negative one on sukuk risk. Furthermore, whereas sukuk risk cannot mediate the impact of corporate liquidity on sukuk yield, it can mediate the impact of corporate leverage on sukuk yield. The research's implication is that it is not necessary to avoid taking on larger sukuk risk in order to raise company leverage by boosting capital structure.